Animersion an immersion to gender discourse in the world of anime - Afdal, Christine Charmaine S.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
The main objective of this research is to determine how male and female audiences understand masculinity and femininity in the Anime Ah My Goddess! To be able to do this, the researcher uses a multi-method approach (Content Analysis, Focus Group Discussion and Focus Interview) in gathering the information she believes is relevant. As a guide to her data gathering, analysis and interpretation, the researcher uses the Hexagon Model of Audience Reception and Media Use. This model is an integration of the main principles of these three communication models: (1) Expectancy Value Model of Gratification Sought and Obtained; (2) Model of Viewer and Media Influence on Media Use; and (3) Cognitive Approach to the Reception of Meaning. This study is yet another confirmation to the notion that male reception and female reception of gender-related messages differ. Animersion shows that male defines femininity in ways that flatter the male sex. The female informants, on the other hand, define femininity as a simple awareness of sexual preference. Despite the difference, Animersion also shows that they have similarities in reception. For instance, neither male nor female interpreted masculinity as the dominating. Yet, it has been subtly implied that the female character, Belldandy, is subordinate by choice, not by force. Animersion provides relevant insights on how an audience interprets gender-related messages in an Anime. This research also provides insights on affecting audience reception.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Ah My Goddess, Anime -- Philippines -- Masculinity; Ah My Goddess, Anime -- Philippines -- Femininity